Challenges and Opportunities Associated With Platelets in Pancreatic Cancer - Chen, Zhou; Wei, Xiaodong; Dong, Shi; Han, Fangfang; He, Ru; Zhou, Wence (Frontiers in Oncology, 2022)
Pancreatic cancer is one of the most malignant tumors with poor prognosis in digestive system. Innovative molecular mechanisms and therapies of pancreatic cancer are urgently-needed, meanwhile, are full of great challenges. Interestingly, platelets, in addition to playing a crucial role in coagulation, also contribute to the growth, invasion and metastasis of various tumors, including pancreatic cancer. This narrative review presents current knowledge and recent findings on the impact of platelets on pancreatic cancer, including platelet-related molecular mechanisms of cancer promotion, pancreatic cancer fibrosis, immune evasion, mechanisms of drug resistance, thrombosis, targeted platelet therapy, combined radiotherapy and chemotherapy treatment and platelet combined with nanotechnology treatment. Advances in our understanding of platelets in pancreatic cancer contribute to the identification of new therapeutic targets and the rapid development of frontier clinical trials.